What Einstein told his cook 2 : the sequel : further adventures in kitchen science - Wolke, Robert L.; Wolke, Robert L. (New York : Norton, 2005)
Bridges the gap between chemistry and cooking, using plain language to describe the chemistry behind numerous kitchen phenomena and to debunk many commonly held myths.
Includes index.
Sequel to: What Einstein told his cook. 2002.
Publisher's Weekly.
Publisher's Weekly, March 2005.
Adult
Keywords: Cooking; Science -- Miscellanea; Cooking; Science -- Miscellanea